The Influence of Gusjigang Local Wisdom (Gus) on Developing Students' Sense of Responsibility During School Competitions at SD 1 Barongan - FaiZ, Moh. Najibul; Rondli, Wawan Shokib; Santoso, Denni Agung (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study examines whether integrating the 'Gus' (good character) value of Gusjigang local wisdom is associated with changes in elementary students' responsibility during school competition activities. A quantitative pre-experimental one-group pretest-posttest design involved all 48 students participating in FLS2N, FTBI, OSN, POPDA, and MAPSI at SD 1 Barongan. Responsibility was measured using a 25-item questionnaire administered before and after the intervention. Instrument validity and reliability were examined, followed by Shapiro-Wilk normality tests and a paired-samples t test. The pretest and posttest data were normally distributed (p = .797 and p = .852). Posttest scores were significantly higher than pretest scores, t(47) = -106.520, p < .001, with a mean paired difference of -21.312. Pretest and posttest scores were also strongly correlated (r = .967, p < .001). Within the limitations of a single-group design, these findings indicate that culturally grounded moral reinforcement through Gusjigang can support responsibility, discipline, and sportsmanship during competition preparation. The study contributes an applicable local-wisdom-based framework for character development in elementary schools.